Advance Research Directives: Dementia Researchers' Views on a Prototype Directive and Implementation Strategies. Issue 3 (21st May 2021) - Ries, Nola; Mansfield, Elise
ABSTRACT: Advance research directives (ARDs) enable people to document preferences for future research participation in the event of incapacity. This article reports on interviews with 11 dementia researchers in Australia that focused on the content of a prototype ARD and processes for making and using ARDs. Participants agreed that an ARD template should provide information to explain research and the rationale for making a directive, allow the person to nominate trusted individuals to be involved in future decisions, and record the person's general willingness or unwillingness to be involved in research. Providing a list of various research activities elicits preferences and risk tolerances in more detail. Priority groups for ARD implementation include people with a diagnosis involving progressive cognitive impairment and people interested in research. Researchers and health and legal professionals have a role in promoting ARDs. Our findings suggest that, as a voluntary strategy, ARDs could promote appropriate inclusion in research.